PENYIARAN ONLINE LANGKAH PELESTARIAN BUDAYA DAERAH - Riki Rikarno (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2020)
The development of information and communication technology is very fast in this era of globalization. This development is sure to touch, even give birth to a new orientation in all areas of human life including the art performance of saluang dendang. One of the Baguruau Saluang Dendang groups in Solok Regency is Cimpago Talang. The Cimpago Talang arts club, with the Covid 19 concession, the government has implemented social restrictions. For this reason, broadcasting media through social media applications is an option for performing saluang dendang shows. One of the media they use is Live Streaming via the Facebook and Youtube applications, so that the Baguruau Saluang Dendang performance continues with the concept of two-way communication with the audience.ABSTRAKPerkembangan teknologi informasi dan komunikasi sangat cepat pada era globalisasi ini. Perkembangan ini dipastikan menyentuh, bahkan melahirkan orientasi baru pada semua bidang kehidupan manusia termasuk pertunjukan kesenian saluang dendang. Salah satu grub Baguruau Saluang Dendang yang ada di Kabupaten Solok adalah Cimpago Talang. Grub kesenian Cimpago Talang dengan konsidi Covid 19, pemerintah telah menerapkan pembatasan social. Untuk itu media penayangan melalui aplikasi-aplikasi media social menjadi pilihan melakukan pertunjukan saluang dendang. Salah satu media yang mereka pakai adalah live streaming melalui aplikasi Facebook dan Youtube, sehingga pagelaran baguruau saluang dendang tetap berjalan dengan konsep komunikasi dua arah dengan penonton.Kata Kunci: Penyiaran Online, Kesenian Saluang Dendang, Kelompok Seni Cimpago Talang